2019
DOI: 10.1016/j.compstruct.2019.110999
|View full text |Cite
|
Sign up to set email alerts
|

An extended cohesive damage model study of geometrical ratio effects on failure mechanisms of functionally graded sandwiches with multi-layered cores

Abstract: An investigation of geometrical ratio effects on failure mechanisms of functionally graded sandwiches with multi-layered cores (FGSMLC) is presented in this paper. The extended cohesive damage model (ECDM) is used in detailed investigations of geometrical ratio effects on the failure mechanisms of the FGSMLC under three-point bending. The ECDM prediction shows very good agreements with previous experimental work. The ECDM prediction reveals that the FGSMLC with 8-layered graded cores shows loading capacities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…e present solution is compared with the Kirchho -Love (KL) solution [26], respectively. e parameters in the FG plate are xed at q(x,y) sin(πx/a)sin(πy/b) N/ mm 2 , a b 1000 mm, ∆h 0.2 mm, k 2 0, E 3 0 1 1 s, h 1 :h 2 :h 3 1 : 2:1, and k 3 −k 1 .…”
Section: Validation Of the Present Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…e present solution is compared with the Kirchho -Love (KL) solution [26], respectively. e parameters in the FG plate are xed at q(x,y) sin(πx/a)sin(πy/b) N/ mm 2 , a b 1000 mm, ∆h 0.2 mm, k 2 0, E 3 0 1 1 s, h 1 :h 2 :h 3 1 : 2:1, and k 3 −k 1 .…”
Section: Validation Of the Present Solutionmentioning
confidence: 99%
“…Tornabene et al [24,25] used the higher-order theory to study the dynamic behavior of anisotropic doubly curved shells. An extended cohesive damage model was proposed by Ghimire and Chen [26] for the analysis of geometrical ratio in uences on the failure mechanisms of FG sandwiches, and they found that the layered core can provide significant improvements in loading capacity. On the basis of the four-variable plate theory, Trinh el al.…”
Section: Introductionmentioning
confidence: 99%